Challenges for the South African tourism industry to the year 2010 based upon a Delphi market research project - Jonathan Z. Bloom; Marius Leibold (South African Journal of Business Management, 1994)
The South African tourism industry is expected to develop substantially over the next fifteen years, due to anticipated high tourism market growth rates. However, tourism demand is subject to a host of uncontrollable factors, which are difficult to measure and project. Despite this fact, the tourism industry of a country, including both private sector and public sector operators, needs scientifically accepted projection bases to make investment and other strategic decisions. In this article we aim to convey the results and recommendations of an empirical study based on the Delphi research model, and to indicate the implications thereof for future national tourism strategies of South Africa. The approach, methodology and techniques used in the research are relevant to researchers internationally, and the recommendations are useful for national tourism policy and strategy formulation in any geographical context.
Keywords: 650